2020
DOI: 10.1108/apjml-01-2020-0053
|View full text |Cite
|
Sign up to set email alerts
|

Generating customer engagement in electronic-brand communities: a stimulus–organism–response perspective

Abstract: PurposeThis article investigates the factors in customer engagement with electronic brand (e-brand) communities and the mechanism behind their effects. The aim is to investigate the influence of various characteristics of e-brand communities on customer engagement, satisfaction through brand loyalty, and Recommendation.Design/methodology/approachA survey questionnaire was administered to 320 Facebook users in Pakistan. The aim is to investigate the influence of various characteristics of e-brand communities on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 110 publications
2
48
0
1
Order By: Relevance
“…Users will be willing to recommend MQP to others due to their favorable perceptions, approval, judgment and past experience. Prior studies mentioned that RI is motivated by satisfaction toward electronic-brand communities (Naqvi et al , 2020). RI is viewed as an essential post-adoption behavior that is necessary to diffuse an innovation (Verkijika, 2018).…”
Section: Hypotheses Formation and Research Modelmentioning
confidence: 99%
“…Users will be willing to recommend MQP to others due to their favorable perceptions, approval, judgment and past experience. Prior studies mentioned that RI is motivated by satisfaction toward electronic-brand communities (Naqvi et al , 2020). RI is viewed as an essential post-adoption behavior that is necessary to diffuse an innovation (Verkijika, 2018).…”
Section: Hypotheses Formation and Research Modelmentioning
confidence: 99%
“…(1) To explore the impact of perceived usefulness and ease of use on attitude In the study of TAM research, it can be found that perceived usefulness, perceived ease of use, and attitude can effectively and significantly affect users' or consumers' behavioral intentions [19,20]. The subjective norms for the personal use of information technology products will also be affected by external factors or others [21] because new high-tech products with sufficient and complete information are the main factors affecting the control of perceptual behavior [16]. Based on the above-mentioned literature discussion, the hypotheses of this research were as follows:…”
Section: Purpose Of the Study The Research Objectives Were As Followsmentioning
confidence: 99%
“…The internal response takes the form of the consumers' attitude, while the external response takes the consumers' specific behavior [54]. The consumers' specific behavior may then comprise consumer engagement [55][56][57], impulse buying behavior [52,58,59], purchase intention [45,46,60], or repurchase intention [61].…”
Section: Stimulus-organism-response (Sor) Theorymentioning
confidence: 99%